Inhibition of mitochondrial complex I by the novel compound FSL0260 enhances high salinity-stress tolerance in Arabidopsis thaliana - Sako, Kaori; Futamura, Yushi; Shimizu, Takeshi; Matsui, Akihiro; Hirano, Hiroyuki; Kondoh, Yasumitsu; Muroi, Makoto; Aono, Harumi; Tanaka, Maho; Honda, Kaori; Shimizu, Kenshirou; Kawatani, Makoto; et al. (Scientific reports, 2020)
Chemical priming is an attractive and promising approach to improve abiotic stress tolerance in a broad variety of plant species. We screened the RIKEN Natural Products Depository (NPDepo) chemical library and identified a novel compound, FSL0260, enhancing salinity-stress tolerance in Arabidopsis thaliana and rice. Through transcriptome analysis using A. thaliana seedlings, treatment of FSL0260 elevated an alternative respiration pathway in mitochondria that modulates accumulation of reactive oxygen species (ROS). From comparison analysis, we realized that the alternative respiration pathway was induced by treatment of known mitochondrial inhibitors. We confirmed that known inhibitors of mitochondrial complex I, such as rotenone and piericidin A, also enhanced salt-stress tolerance in Arabidopsis . We demonstrated that FSL0260 binds to complex I of the mitochondrial electron transport chain and inhibits its activity, suggesting that inhibition of mitochondrial complex I activates an alternative respiration pathway resulting in reduction of ROS accumulation and enhancement of tolerance to salinity in plants. Furthermore, FSL0260 preferentially inhibited plant mitochondrial complex I rather than a mammalian complex, implying that FSL0260 has a potential to be an agent for improving salt-stress tolerance in agriculture that is low toxicity to humans.